Global Role for Polyadenylation-Assisted Nuclear RNA Degradation in Posttranscriptional Gene Silencing - Wang, Shao-Win (American Society for Microbiology (ASM), 2008)
Fission yeast Cid14, a component of the TRAMP (Cid14/Trf4-Air1-Mtr4 polyadenylation) complex, polyadenylates nuclear RNA and stimulates degradation by the exosome for RNA quality control. Here, we analyze patterns of global gene expression in cells lacking the Cid14 or the Dis3/Rpr44 subunit of the nuclear exosome. We found that transcripts from many genes induced during meiosis, including key regulators, accumulated in the absence of Cid14 or Dis3. Moreover, our data suggest that additional substrates include transcripts involved in heterochromatin assembly. Mutant cells lacking Cid14 and/or Dis3 accumulate transcripts corresponding to naturally silenced repeat elements within heterochromatic domains, reflecting defects in centromeric gene silencing and derepression of subtelomeric gene expression. We also uncover roles for Cid14 and Dis3 in maintaining the genomic integrity of ribosomal DNA. Our data indicate that polyadenylation-assisted nuclear RNA turnover functions in eliminating a variety of RNA targets to control diverse processes, such as heterochromatic gene silencing, meiotic differentiation, and maintenance of genomic integrity.